Assessment of Linezolid Efficacy, Safety and Tolerability in the Treatment of Tuberculosis: A Retrospective Case Review - Alena Tse-Chang; Dennis Kunimoto; Evelina Der; Rabia Ahmed (Canadian Journal of Infectious Diseases and Medical Microbiology)
Linezolid is a potentially effective drug for the treatment of patients with drug-resistant tuberculosis. Among 13 patients treated for tuberculosis with linezolid in the present study, nine had treatment success and four remain on treatment. Adverse effects occurred in 11 (85%) patients, of whom three discontinued treatment because of adverse effects. The present study adds to the growing evidence supporting the efficacy of linezolid for tuberculosis, although treatment remains complicated by adverse effects.